Case Report: A rare case of familial lung cancer requiring pneumonectomy in three male siblings - Kaprin, Andrey; Pikin, Oleg; Ryabov, Andrey; Aleksandrov, Oleg; Toneev, Evgeniy; Lubchenko, Ludmila; Zelenova, Ekaterina (Frontiers in Oncology, 2022)
Lung cancer is a disease with a unique genetic pattern and is occasionally related to hereditary syndromes such as Lynch, Louis-Bar, Li-Fraumeni syndrome. In some patients, germinal mutations may be discovered in combination with somatic alterations. For instance, Li-Fraumeni syndrome often reveals a mixture of TP53 and EGFR mutations. The development of new target therapies necessitates an extensive search for new pathogenic mutations. In this article, we present a rare case report of lung cancer, requiring a pneumonectomy, in three sibling brothers.